Measurement of the B(0) lifetime with partially reconstructed B(0)-->D(-)l(+)nu(l) decays. - Aubert, B; Boutigny, D; Gaillard, J; Hicheur, A; Karyotakis, Y; Lees, J; Robbe, P; Tisserand, V; Zghiche, A; Palano, A; Pompili, A; Chen, G; et al. (2002)
The B(0) lifetime was measured with a sample of 23 million BB pairs collected by the BABAR detector at the PEP-II e(+)e(-) storage ring during 1999 and 2000. Events from the semileptonic decay B(0)-->D(*-)l(+)nu(l) have been selected with a partial reconstruction method in which only the charged lepton and the slow pi from the D*--->D(0)pi(-) decay are reconstructed. The result is tau(B(0)) = 1.529+/-0.012(stat)+/-0.029(syst) ps.